HUBUNGAN STATUS GIZI DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA PUSKESMAS AIR TIRIS - GUSMAN VIRGO; NUR CHOLISAH; INDRAWATI INDRAWATI (Universitas Pahlawan Tuanku Tambusai, 2022)
Good nutritional status will have a very important value for maintaining body processes in growth and development, especially guarding the body against various infectious diseases.Acute Respiratory Tract Infection (ARI) is the cause of 2/3 of under-five deaths due to infectious diseases worldwide. In Indonesia, under-five deaths due to ARI have increased by 20.6% from 2019 to 2020. In Kampar Regency, the incidence of ARI in 2020 was 46,496 cases with the highest incidence at the Air Tiris Health Center as many as 1840 cases. In the Air Tiris Health Center area, Batu Belah village is the highest incidence of ARI with 450 cases. The purpose of this study was to determine the relationship between nutritional status and the incidence of ARI in children under five in Batu Belah Village, Air Tiris Health Center Working Area in 2021. Design This research is an analytic survey with a cross sectional research design. The population of this study were all medical records of children under five who experienced ARI at the Air Tiris Health Center. The sampling technique used a total sampling of 94 people. Research instrument with checklist sheet. The data analysis used is univariate and bivariate with chi square test. The results showed that poor nutritional status was associated with the incidence of ARI in the frequent category, namely 45 people (47.9%), and for the rare category, 3 people (3.2%). Measure the test X2 = 44.168 with a value of p = 0.000 (p < 0.05). So there is a significant relationship between nutritional status and the incidence of ARI in children under five in Batu Belah Village, Air Tiris Health Center Work Area 2021. It is recommended that this study recommend that the provision of information on ARI to be further improved by health workers.Â Â